(untitled) (Al-Academy, 2021)
The internal administrative spaces of the interior designer formed an obsession for their development and for finding solutions and treatments to advance to enhance the state of adaptation for their employees by providing a healthy, appropriate and sound environment for work and production. . The first chapter focuses on laying theoretical foundations to show what health materials are used in the administrative spaces of the training directorates of the Ministry of Education in Baghdad. The second chapter dealt with the knowledge of health materials, their impact and effectiveness in the interior space, and the variables of their functional characteristics and their work in the interior spaces in a way that enhances the development of the role of interior design and shows the extent of the positivity of the material and its properties, and come up with important indicators, while the third chapter included a description and analysis of research models within the axes of analysis in the analysis form While the fourth chapter ends with the most prominent results and conclusions with reference to the most important recommendations related to the topic of the research.